Photophysical Properties of Novel Phthalocyanines: Multi Emission by Excited at Short Wavelength - ZHAO, PENG; PARK, YONG-SUNG; WOO*, JE-WAN (Asian Journal of Chemistry, 2024)
Two novel phthalocyanines: tetra-azobenzene substituted zinc phthalocyanine ZnPc.(Oazo)4 and polymeric ytterbium phthalocyanine carboxyl (YbPPc.COOH) have been synthesized and their electronic adsorption and emission spectra have been investigated by spectrometric method. Both of the synthesized compounds can emit two fluorescent peaks when excited at short wavelength (below 400 nm) and one peak when excited at long wavelength (higher than 600 nm) as well. For YbPPc.COOH, in pH 7.4 buffer solution, when excited at 330 nm, beside normal fluorescent peak at 720 nm, a second emission peak appeared at 455 nm. The fluorescence quantum yield of two emission was 0.35 (720 nm em, 635 nm ex) and 0.33 (455 nm em, 330 nm ex), respectively. This equivalent multi-emission phenomenon by different excited wavelength indicates good applied potential in photodynamic diagnose and fluorescence imagination.